SSR Markers in Genetic Diversity Assessment of Fig Ficus carica L. Populations in Kurdistan Region – Iraq - Hussein, Abdulqader E.; Jubrael, Jaladet M.S. (Science Journal of University of Zakho, 2020)
In the current study, simple sequence repeats (SSR) markers were used to assess the phylogenetic relationships and to investigate genetic polymorphism among 28 fig landraces in Kurdistan Region-Iraq. Fifteen SSR loci produced 73 alleles were produced across all studied genotypes. The observed heterozygosity (Ho) was (0.000) detected with all primers. The expected heterozygosity (He) was ranged from 0.000 to 0.875. The Polymorphic information content PIC was ranged from 0.000 to 0.843, and Fixation index values were ranged from +0.999 to +1.000. The SSR profiles produced were further used for assessing similarities (genetic distance) between the cultivars studied. Genetic distance calculation was achieved using computer software (NTSYS-PC). The genetic distances among the studied genotypes were ranged between (0.1029-0.9485). Genetic distances were supported by the developed dendrogram using UPGMA method. This dendrogram was split into two major groups, and each group was further divided into subgroups. The product of the general data and study of the clusters suggested that almost all the fig cultivars revealed significant genetic diversities. The microsatellite markers allowed clearly the differentiation between studied fig landraces and gave the reliability of these markers in fingerprinting of fig genotypes. It is worth to mention that the study findings will help the management of fig genotypes and might help the selection of landraces for future breeding program in this region.